2021
DOI: 10.1021/acs.jpcc.1c02216
|View full text |Cite
|
Sign up to set email alerts
|

Direct Dynamics Simulations of Hyperthermal O(3P) Collisions with Pristine, Defected, Oxygenated, and Nitridated Graphene Surfaces

Abstract: We report here an extensive direct dynamics study on the collisions of hyperthermal (14.9 kcal mol–1) atomic oxygen with a variety of graphene surfaces to explore possible reaction channels. Several models, ranging from pristine graphene to graphene with defects and with different extents of oxidation and nitridation, are investigated. The impinging oxygen atom is found to form various surface oxygenated species, such as epoxides, ethers, and lactones, as well as gaseous species, such as CO, CO2, O2, N2, CN, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 71 publications
(226 reference statements)
3
18
0
Order By: Relevance
“…Hase and co-workers modeled the collisional dynamics of N 2 with graphite at collision energies of 26 and 60 kJ mol –1 and found that for all incidence angles, single collision scattering is the dominant process; at the lower collision energy (similar to what is used in our work here) close to normal incidence angles, roughly 50% of the initial translational energy is channeled away, primarily to the graphene surface vibrational modes . This was taken one step further by Nieman et al and Jayee et al in their primarily modeling studies of the reaction of N­( 4 S) and O­( 3 P) atoms with graphene, though at vastly higher collision energies relevant to the reentry of spacecrafts into Earth’s atmosphere. , Both the high collision energy as well as the fact that a reactive atomic species is scattered off graphene cause not only nonreactive scattering to be observed but also reactions with the graphene itself (functionalization), and the formation of ablation products such as CN radicals in the gas-phase. Juaristi and co-workers modeled the scattering of O 2 off HPOG by ab initio molecular dynamics at lower collision energies of ∼20 kJ mol –1 , focusing on the effects of the initial alignment of the impinging O 2 molecule …”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Hase and co-workers modeled the collisional dynamics of N 2 with graphite at collision energies of 26 and 60 kJ mol –1 and found that for all incidence angles, single collision scattering is the dominant process; at the lower collision energy (similar to what is used in our work here) close to normal incidence angles, roughly 50% of the initial translational energy is channeled away, primarily to the graphene surface vibrational modes . This was taken one step further by Nieman et al and Jayee et al in their primarily modeling studies of the reaction of N­( 4 S) and O­( 3 P) atoms with graphene, though at vastly higher collision energies relevant to the reentry of spacecrafts into Earth’s atmosphere. , Both the high collision energy as well as the fact that a reactive atomic species is scattered off graphene cause not only nonreactive scattering to be observed but also reactions with the graphene itself (functionalization), and the formation of ablation products such as CN radicals in the gas-phase. Juaristi and co-workers modeled the scattering of O 2 off HPOG by ab initio molecular dynamics at lower collision energies of ∼20 kJ mol –1 , focusing on the effects of the initial alignment of the impinging O 2 molecule …”
Section: Introductionsupporting
confidence: 59%
“…15 relevant to the reentry of spacecrafts into Earth's atmosphere. 16,17 Both the high collision energy as well as the fact that a reactive atomic species is scattered off graphene cause not only nonreactive scattering to be observed but also reactions with the graphene itself (functionalization), and the formation of ablation products such as CN radicals in the gasphase. Juaristi and co-workers modeled the scattering of O 2 off HPOG by ab initio molecular dynamics at lower collision energies of ∼20 kJ mol −1 , focusing on the effects of the initial alignment of the impinging O 2 molecule.…”
Section: Introductionmentioning
confidence: 99%
“…The scattering of hydrogen off graphene has already been investigated both experimentally and theoretically. [10][11][12] The scattering of atoms other than hydrogen (N( 4 S) and O( 3 P), respectively) with graphene has also been modelled by Nieman et al and Jayee et al; [13,14] quantum-methods guaranteed that chemical reactions with the graphene (insertion) and ablation reactions could be observed.…”
Section: Introductionmentioning
confidence: 98%
“…and Jayee et al . ;[ 13 , 14 ] quantum‐methods guaranteed that chemical reactions with the graphene (insertion) and ablation reactions could be observed.…”
Section: Introductionmentioning
confidence: 99%
“…The modification of graphene by chemical reactions on its surface to form covalent bonds is technologically important as such functionalizations can introduce a tunable band gap (pristine graphene is a zero band gap material), , and scattering studies of graphene can reveal the fundamentals of the collision process and the potential bond-formation process on the graphene surface. While much of the experimental and computational work focused on translational energy and angular distributions of the scattered particles (the only possible degree of freedom for atomic collisions), Juaristi and co-workers, Rutigliano and Pirani, and Hase and co-workers also explored the rotational state distribution of O 2 and N 2 scattered off graphite. Hase and co-workers found that only a small fraction of the available energy is channeled into rotations but none into vibrations.…”
Section: Introductionmentioning
confidence: 99%